2019
DOI: 10.1021/acs.inorgchem.9b01565
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Movement of Zn2+ Ions with Zero-Strain Characteristic: Clarifying the Reaction Mechanism of Li2ZnTi3O8

Abstract: Lithium zinc titanate spinel, Li2ZnTi3O8, has received significant attention as a negative electrode material for lithium-ion batteries (LIBs). However, its reaction mechanism has not been fully clarified yet, particularly for the large voltage hysteresis between discharge and charge curves. We hence closely examined (Li1–x Zn x )­[Li1/3+x/3Ti5/3–x/3]­O4 (LZTO) with 0 < x ≤ 0.5 by measuring its open-circuit voltage (OCV) and recording synchrotron radiation X-ray diffraction (XRD) patterns. Here, LZTO is a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
63
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(72 citation statements)
references
References 35 publications
4
63
5
Order By: Relevance
“…11 Owing to this opposite a c trend in the discharge process, the a c value of x = 0.25 [=8.3645(1) Å] in the initial state agreed substantially with that in the discharged state. 11 This means that the x = 0.25 sample is regarded as a perfect zero-strain material with ΔV c = 0%. The characteristic of perfect zero strain is ideal for all-solid-state LIBs, in which robust solid−solid interfaces are required for fast and stable Li conduction.…”
Section: ■ Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…11 Owing to this opposite a c trend in the discharge process, the a c value of x = 0.25 [=8.3645(1) Å] in the initial state agreed substantially with that in the discharged state. 11 This means that the x = 0.25 sample is regarded as a perfect zero-strain material with ΔV c = 0%. The characteristic of perfect zero strain is ideal for all-solid-state LIBs, in which robust solid−solid interfaces are required for fast and stable Li conduction.…”
Section: ■ Introductionmentioning
confidence: 82%
“…Ex situ synchrotron XRD measurements indicated that the a c value of x = 0.125 slightly decreased from 8.3622(1) to 8.3514(1) Å in the fully discharged state, whereas that of x = 0.5 slightly increased from 8.3688(1) to 8.3816(1) Å. 11 Owing to this opposite a c trend in the discharge process, the a c value of x = 0.25 [=8.3645(1) Å] in the initial state agreed substantially with that in the discharged state. 11 This means that the x = 0.25 sample is regarded as a perfect zero-strain material with ΔV c = 0%.…”
Section: ■ Introductionmentioning
confidence: 88%
See 3 more Smart Citations